An Exploration Research about Sourdough Bread as Delight Culinary - Ichwan, Odelia Valda; Budi Darma, Priscilla Patricia; Astiti Putri, Ni Wayan Ari; Padma Wulandari, Ni Putu Putri; Maulana, Irfan; Emmanuel, Johnatan Christian; Santi Diwyarthi, Ni Desak Made (Jurnal Multidisiplin West Science, 2024)
The objective of this study is to investigate Sourdough bread. Employing a qualitative methodology with descriptive research. The research conducted depth-interview with three senior lecturers from Politeknik Pariwisata Bali, participant observation, and literature study regarding Sourdough bread. The analysis conducted utilizes the data triangulation that uses multiple data sources, data collection techniques, or theories to validate and strengthen research findings. Sourdough bread possesses several distinctive qualities that make it a favorite among many people. These include its complex flavor and aroma, unique texture, natural preparation process, health benefits, rich history and tradition, personal and artistic elements, and long shelf life. Research on sourdough bread is essential for understanding consumer preferences, driving innovation, and adapting to market demands.